Breaking silence : a novel of Serrated Edge - Lackey, Mercedes; Martin, Cody, 1987- (Serrated edge, 2020)
"When Staci was first shunted off to the backwater town of Silence, Maine, to live with her alcoholic mother, she thought her life was over. Silence had none of the amenities a typical teen in the twenty-first century considered essential: no cell service and barely any internet connectivity. But Staci soon learned that Silence was more than a town left behind by progress. The first family of Silence, the Blackthorns, liked the town that way. The Blackthorns were dark elves who fed off the misery of the residents of Silence. But now, all that's changing for the better. With the help of Staci and her friends, the Blackthorns have been all but defeated. Industry is returning to Silence, and Staci's mom is improving with each passing day. There's even a cute new busboy at the diner. But evil dies hard. And Staci, now a mage-in-training, senses that the Blackthorns have not yet given up the fight. The soul of Silence is on the line, and it is up to Staci and her friends to fight back against the encroaching darkness"--